2020
DOI: 10.1002/adom.202001349
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐Dependent Exciton Modulation Characteristics of 2D MoS2 Driven by Acoustic Waves

Abstract: Acoustic waves were recently utilized to modulate and control the electronic, optical, and magnetic properties of 2D materials. Among 2D materials, the mechanically exfoliated MoS2 with a perfect crystal structure provides an ideal platform to study its exciton characteristics. However, layer‐dependent exciton modulation characteristics of the 2D materials are still not systematically investigated under acoustic waves. Here, the in situ confocal fluorescence spectroscopy is used to probe the behavior of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…122 This intrinsic piezo-electricity may be quite promising in improving the electron-hole dissociation efficiency in photovoltaic cells. In 2021, Sheng et al 123 further demonstrated that the exciton characteristics strongly depend on the layer numbers of MoS 2 sheets. Under acoustic excitations, the PL quenching in odd MoS 2 layers is remarkably larger than that in even layers without piezo-electricity.…”
Section: B Acoustic Exciton Modulationmentioning
confidence: 99%
“…122 This intrinsic piezo-electricity may be quite promising in improving the electron-hole dissociation efficiency in photovoltaic cells. In 2021, Sheng et al 123 further demonstrated that the exciton characteristics strongly depend on the layer numbers of MoS 2 sheets. Under acoustic excitations, the PL quenching in odd MoS 2 layers is remarkably larger than that in even layers without piezo-electricity.…”
Section: B Acoustic Exciton Modulationmentioning
confidence: 99%
“…Hence, 2D materials provide the most suitable arena for researchers to explore and inspire new device concepts and designs in ICs. Furthermore, 2D materials possess layered microstructures, [26,27] large specific surface area, [28][29][30] and sensitive optical−acoustic−thermal−electrical− mechanical sensing responses, [31][32][33][34][35][36] enabling the integration of multi-functionality to achieve in-memory computing (IMC), [14] in-sensor computing (ISC), [37] and even all-in-one sensingmemory-computing (SMC) fusion. As such, the introduction of silicon-compatible 2D materials can ease the challenges in ICs and create advanced technologies beyond von Neumann architecture, which contribute to the evolution of next generation ICs with high density, energy efficiency, and performance.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of high-quality, few-layer TMDCs is of significant interest and importance to both fundamental studies and various potential applications. Therefore, the exfoliation of MoS 2 crystals into few/monolayer nanosheets represents a critical step toward achieving the high optical activity required for construction of high-performance devices. Various physical and chemical synthesis methods have been developed to prepare few-layer MoS 2 nanosheets with valuable properties, such as chemical exfoliation through ion intercalation, thermal ablation, chemical vapor deposition on substrates, direct solvothermal synthesis, micromechanical cleavage, and liquid-phase exfoliation (LPE). However, chemical exfoliation through ion intercalation can alter the crystal structure and thus destroy the semiconducting nature and affect the electrical and optoelectronic characteristics of MoS 2 nanosheets. Chemical vapor deposition, solvothermal synthesis, and micromechanical cleavage methods are high-energy, time-consuming processes and are thus unsuitable for fast, economical, large-scale production of few-layer MoS 2 nanosheets.…”
Section: Introductionmentioning
confidence: 99%